Report of the Team from the Planning Commission of India on their visit to Trinidad and Tobago in September 1961 - Planning Commission (Planning Commission, 1961)
The Premier of Trinidad, Dr. Eric Williams, during his visit to India, in June, 1961, had stated that this Government would like a small team from the Planning Commission, consisting of an economist, an engineer and administrator with knowledge of community development to visit this country for a fortnight to study the operation of their development plans in order to make an assessment of their organisational structure, planning techniques and personnel requirements.
Planning Commission
Planning Commission